Multimodale Interaktionsanalyse Konzeptualisierung von Integration bei Brasilianer:innen in Deutschland - Ladilova, Anna (De Gruyter, 2023)
How do Brazilians in Germany experience the integration process? This volume investigates this question using a method that analyzes conversations multimodally - i.e., by incorporating gestures - and sets them in relation to their social context. Its findings provide exciting insights into the situation of this group, which has largely been overlooked by previous research, and reveal how integration can succeed.